Congenital cystic adenomatoid malformation in adults detected after infection. Issue 8 (14th September 2018) - Kagawa, Hiroyuki; Miki, Keisuke; Miki, Mari; Urasaki, Koji; Kitada, Seigo
Abstract : Congenital cystic adenomatoid malformation (CCAM) is a benign congenital tumour in which a part of the lung becomes polycystic. Case 1 was a 64‐year‐old male who was diagnosed with pneumonia, with multiple cysts in the right lower lung lobe, using chest computed tomography (CT). After treatment of the pneumonia, including Mycobacterium abscessus, a right lower lobectomy was performed. Case 2 was a 41‐year‐old male who had suffered from pneumonia many times since his youth. Polycystic and infiltrative shadows were observed on chest CT. After treatment of the pneumonia, a right lower lobectomy was performed. Pathologically, both the cases were diagnosed as CCAM type 1. Although CCAM in adults is very rare, it should be considered in the differential diagnosis of cases with repeated pneumonia due to suspected congenital cystic disease. CCAM is better detectable with chest CT and requires active surgical treatment. Abstract : Congenital cystic adenomatoid malformation (CCAM) is a benign congenital tumour in which a part of the lung becomes polycystic. Although CCAM in adults is very rare, it should be considered in the differential diagnosis of cases with repeated pneumonia due to suspected congenital cystic disease. CCAM is better detectable with chest computed tomography and requires active surgical treatment.